Comparison and phylogenetic analysis of the heat shock protein 70 gene of Babesia parasites from dogs - Yamasaki, Masahiro; Inokuma, Hisashi; Sugimoto, Chihiro; Shaw, Susan E.; Aktas, Munir; Yabsley, Michael J.; Maede, Yoshimitsu (Elsevier Science Bv, 2007)
The heat shock protein 70 (hsp70) genes of Babesia gibsoni, B. canis canis, B. canis vogeli, and B. canis rossi isolated from infected dogs were cloned by polymerase chain reaction (PCR) and sequenced. In the nucleotide sequence and the predicted amino acid sequence of the gene, the parasites were very similar to each other. The nucleotide sequences of the hsp70 gene had more variety than those of 18S nuclear subunit ribosomal DNA (18S rDNA). A phylogenetic analysis of these sequences and comparisons with sequences from other Babesia and Theileria species revealed that all canine babesial isolates analyzed in the present study were closely related to each other and formed one cluster. Additionally, a phylogenetic analysis of Babesia and Theileria species showed that these parasites could be divided into three groups: group A including canine babesial isolates, B. divergens, B. odocoilei, B. bovis, B. caballi, and B. ovis; group B including Theileria annulata, T orientalis, and T cervi; and group C including B. microti and B. rodhaini. These results suggested that a phylogenetic analysis of the hsp70 gene sequence might be helpful in classifying Babesia and Theileria species, and that canine babesial isolates might be closely related to each other, indicating their evolution from the same ancestry. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Babesia gibsoni; Babesia canis vogeli; Babesia canis canis; Babesia canis rossi; heat shock protein 70; phylogenetic analysis